Effects of sodium alginate‐based coating pretreatment on drying characteristics and quality of heat pump dried scallop adductors. (11th May 2019) - Shi, Qilong; Tian, Yuan; Zhu, Lanlan; Zhao, Ya
Abstract: Background: Drying efficiency and quality maintenance are the major concerns of both manufactures and consumers. Heat pump drying (HPD) is suitable for heat sensitive foodstuffs due to its ability to independently control the drying operation parameters. However, lower drying rate and energy efficiency in the later period of HPD are the bottlenecks that restrain its application. A novel approach using hydrocolloids as pretreatment coatings prior to drying was designed to solve these problems. The effects of sodium alginate (SA) coating, drying temperatures and air velocities on the drying characteristics and quality attributes of scallop adductors were evaluated. Results: Drying took place in the falling rate period. Drying time decreased with increasing temperature, air velocity and SA coating. The Two Term model and the Wang and Singh model gained the best fit for thin‐layer drying of scallop adductors and SA film, respectively. Effective moisture diffusivity increased with temperature, velocity and SA coating and were in the range 7.352–14.620 × 10 −11, 9.890–17.100 × 10 −11 and 2.348–4.604 × 10 −10 m 2 s −1 for uncoated scallop adductors, SA coated scallop adductors and SA films, respectively. The activation energies for SA films, coated and uncoated scallop adductors were 17.07, 20.78 and 26.17 kJ mol −1, respectively. Dried scallop adductors with SA coating pretreatment exhibited a significant lower value of shrinkage rate and hardness, and higher value of toughness than uncoated ones at 30 °C and 2.0 m s −1 ( P < 0.05). Conclusion: Hydrocolloid coating is a promising pretreatment in improving HPD efficiency and enhancing quality attributes of dried scallop adductors. © 2019 Society of Chemical Industry